A comercialização do artesanato Sateré-Mawé em Parintins-AM - Oliveira, Márney Giovane da Silva (Brasil, 2023)
This Course Conclusion Paper is part of the debates on the transformation of indigenous artcrafts into consumer goods for non-indigenous society, addressing the case of Sateré-Mawé artcrafts that are sold in the city of Parintins-AM by the indigenous themselves and also by urban traders. The general objective was to examine the insertion of Sateré-Mawé artcrafts in the Parintins commercial network, highlighting the way the sale of these products has been managed by the indigenous living in the city. The specific objectives were to describe the main historical and cultural aspects of the Sateré-Mawé indigenous people in the municipality of Parintins, specify the artifacts produced by the Sateré-Mawé community and which are destined for commerce outside the village, identify the spaces and situations that, in the context of parintinense, are conducive to the trade of Sateré-Mawé artifacts and to know the role of the Sateré-Mawé indigenous people in the dynamics of commercialization of their products in the city. In terms of methodology, the research was conducted using the Deductive Method, which allowed for a bibliographical survey that prioritized the reading and analysis of books and scientific articles, such as Romano (1982), Lorenz (1992 ), Silva (2011) and Teixeira (2005), and academic works originating from congresses and seminars and which are available on the internet, such as Anselmo Filho et al. (2016) and Rocha (2016), in addition to field research, with on-site visits and informal conversations with non-indigenous traders who trade artifacts of the Sateré-Mawé indigenous people in stores, markets, fairs and with the indigenous person responsible for the Indigenous Transition House and who makes and sells the products in the handicraft shop attached to the house. It was found that the commercialization of Sateré-Mawé artcrafts, as observed in Parintins, has the participation of different agents, circulation environments, consumers and negotiations. Part of this process remains under the control of the indigenous, the other by people who buy their products for resale, informally (street vendors and street vendors) or formally (shops and markets). In the case of the sale made by the Sateré-Mawé, there is a relative insertion in the local commercial circuit, which has its greatest expression in the sales made in the Indigenous Transition House store/workshop, where the families now live. The other points of sale are not fixed and are opportune by the events that take place in Parintins, which prevents marketing outside the Indigenous Transition House earn regularity and generate a significant income.